Bond strength of dual-cured resin cements to root canal dentin - Bruna Junqueira Correa; Aline Evangelista Souza-Gabriel; Fuad Jacob Abi Rached-Junior; Silvio Rocha Correa da Silva; Danielle Cristine Messias (Revista Sul-Brasileira de Odontologia, 2013)
The bonding of dental posts to the root canal walls depends on the resin cement. Objective: This in vitro study assessed the bond strength of resin cements used for post cementation to different root regions. Material and methods: Thirty canine roots were endodontically treated and prepared to receive dental posts which were luted with different resin cements (n = 10): Enforce (Dentsply), Panavia F (Kuraray Dental Co) and RelyX ARC (3M ESPE). The cements were light-cured for 20 s. After cementation, slices from cervical, middle and apical post/root regions were submitted to the push out test in a universal testing machine. The data (MPa) were analyzed using ANOVA and Tukey’s test (a = 0.05). Results: RelyX ARC (3.24 ± 1.49) and Enforce (3.45 ± 1.42) showed higher bond strength than Panavia (0.95 ± 0.39) (p < 0.05), without statistically significant difference between each other (p > 0.05). The bond strength values at the cervical (3.37 ± 1.47) were higher than middle (2.62 ± 1.94) and apical (1.65 ± 0.99) regions (p < 0.05), which were similar between them (p > 0.05). Conclusion: The resin cements RelyX ARC and Enforce presented greater bond strength than Panavia and the bond strength was higher at the cervical region.